2020
DOI: 10.1186/s12931-020-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and cardiorespiratory effects of decreasing lung hyperinflation with budesonide/formoterol in COPD: a randomized, double-crossover, placebo-controlled, multicenter trial

Abstract: Background: Studies suggest that acute decreases in lung hyperinflation at rest improves cardiac function and increases lung vascular perfusion from decompression of a compromised heart. In those studies, changes in resting oxygen uptake induced by medications, an alternative explanation for compensatory increased cardiac function, were not explored.Methods: This double-blind, multicenter, double-crossover study enrolled adults with chronic obstructive pulmonary disease, resting hyperinflation, and > 10% impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…(3) ICS-LABA: LABA-ICS combinations, though not advocated by guidelines as the primary treatment, are often widely prescribed in COPD, especially in primary care practice. Recently, it has been shown that administration of Budesonide/Formoterol results in significant reduction of hyperinflation, an increase in oxygen uptake, and minute ventilation at lower lung volumes, thereby potentially improving cardiac function as well [ 78 ]. A new LABA-ICS combination, fluticasone furoate/vilanterol, has been shown to reduce lung hyperinflation and improve right ventricular end-diastolic volume index, Left ventricular end-diastolic volume, and left atrial end-systolic volume, right ventricular stroke volume, and left atrial ejection fraction versus placebo [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…(3) ICS-LABA: LABA-ICS combinations, though not advocated by guidelines as the primary treatment, are often widely prescribed in COPD, especially in primary care practice. Recently, it has been shown that administration of Budesonide/Formoterol results in significant reduction of hyperinflation, an increase in oxygen uptake, and minute ventilation at lower lung volumes, thereby potentially improving cardiac function as well [ 78 ]. A new LABA-ICS combination, fluticasone furoate/vilanterol, has been shown to reduce lung hyperinflation and improve right ventricular end-diastolic volume index, Left ventricular end-diastolic volume, and left atrial end-systolic volume, right ventricular stroke volume, and left atrial ejection fraction versus placebo [ 79 ].…”
Section: Methodsmentioning
confidence: 99%